2019
DOI: 10.3390/ijerph16050829
|View full text |Cite
|
Sign up to set email alerts
|

Conventional versus Digital Impressions for Full Arch Screw-Retained Maxillary Rehabilitations: A Randomized Clinical Trial

Abstract: Background: The objective of this study was to compare conventional versus digital impressions for Full-Arch maxillary rehabilitations. Methods: Patients selected for this study were treated with full-arch screw-retained rehabilitations supported by six immediately loaded dental implants. Patients have been scheduled randomly into control (conventional impression group, CIG) and test (digital impression group, DIG) groups respectively for a fully conventional workflow and a fully digital workflow. In both grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
94
4
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(113 citation statements)
references
References 52 publications
(69 reference statements)
7
94
4
8
Order By: Relevance
“…AND "loattrfull text"[sb] AND "2009/09/08"[PDat]: "2019/09/05"[PDat])". These keywords have been elaborated by authors in order to lower risk of bias and to obtain a high number of results [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Search Terms Used On Information Sources Were: "(Digital [Almentioning
confidence: 99%
“…AND "loattrfull text"[sb] AND "2009/09/08"[PDat]: "2019/09/05"[PDat])". These keywords have been elaborated by authors in order to lower risk of bias and to obtain a high number of results [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Search Terms Used On Information Sources Were: "(Digital [Almentioning
confidence: 99%
“…Therefore, a recent study reported better accuracy in digital workflows than conventional workflows [15]. Furthermore, digital workflow is being verified as a reliable alternative in clinical practice through clinical trials [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the accuracy of full‐arch digital implant scans. Most of them are in vitro and have shown that digital scans demonstrate comparable accuracy to that of conventional impressions 17‐29 . Additionally, there is a paucity of data in regards to three‐dimensional (3D) printed casts generated from Standard Tesselation Language (STL) files (digital scans) 30 .…”
mentioning
confidence: 99%